2020
DOI: 10.1109/tnnls.2019.2899649
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Computing Universality With Stochastic Inputs

Abstract: The universal approximation properties with respect to L p -type criteria of three important families of reservoir computers with stochastic discrete-time semi-infinite inputs are shown. First, it is proved that linear reservoir systems with either polynomial or neural network readout maps are universal. More importantly, it is proved that the same property holds for two families with linear readouts, namely, trigonometric state-affine systems and echo state networks, which are the most widely used reservoir s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 49 publications
4
60
0
Order By: Relevance
“…In this article, we provide additional insight on the randomization question for another family of RC systems, namely, for the nonhomogeneous state-affine systems (SAS). These systems have been introduced and proved to be universal approximants in [36] and [37]. We here show that they also have this universality property when they are randomly generated.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In this article, we provide additional insight on the randomization question for another family of RC systems, namely, for the nonhomogeneous state-affine systems (SAS). These systems have been introduced and proved to be universal approximants in [36] and [37]. We here show that they also have this universality property when they are randomly generated.…”
mentioning
confidence: 55%
“…It has been shown in [36] and [37] that SAS systems are universal approximants in the fading memory and in the L p -integrable categories in the sense that, given a filter in any of those two categories, there exists an SAS system of type ( 6) that uniformly, or in the L p -sense, approximates it.…”
Section: A Signature State-affine Systemmentioning
confidence: 99%
“…It was shown that any given time-invariant filter (a transformation from u(·) to y(·)) with the fading memory property can be approximated by LSMs to any degree of precision, if L M is chosen from a class of time-invariant filters with fading memory that has a point-wise separation property and f M is chosen from a class of functions that satisfies an approximation property (Maass et al, 2002;. Recent studies have treated the universal approximation property of LSMs and other RC systems in a more mathematically rigorous way (Grigoryeva & Ortega, 2018;Gonon & Ortega, 2018).…”
Section: Basic Frameworkmentioning
confidence: 99%
“…Concerning f act , the properties of ESN, including its universal approximation property, are strictly defined for sigmoid functions [26], [34], [35], [36]. However, in a number of demonstrations [13], [33], using alternative functions, even linear functions, to replace a sigmoid has been shown to be computationally effective.…”
Section: Input Layermentioning
confidence: 99%